"الجملة المعترضة فى القرآن الكريم ـ دراسة بلاغية ـ The Parenthetical Sentences in the Holy Quran - A Rhetorical Study – " - د. صاحب اسلام (الإيضاح, 2016)
This study aims to prove that the Parenthetical Sentences in the Quran are not a way to improve the beauty of literature, but if they appeared in a convenient location they became the requirements of the text. The main findings of this study include the parenthetical sentences in the Holy Quran characterized by specific semantics which is known by the context of Ayat and not only because of assertion, embellishment or clarification. These sentences would inspire the attention from the reciter of Quran to think of the underlying meaning. The parenthetical sentences in Quran cannot be nullified as this will divert the true meaning of Ayat e Kareemas.